Performance Monitoring and Correct Response Significance in Conscientious Individuals - Imhof, Mike F.; Rüsseler, Jascha (Frontiers in Human Neuroscience, 2019)
There is sufficient evidence to believe that variations in the error-related negativity (ERN) are linked to dispositional characteristics in individuals. However, explanations of individual differences in the amplitude of the ERN cannot be derived from functional theories of the ERN. The ERN has a counterpart that occurs after correct responses (correct-response negativity, CRN). Based on the assumption that ERN and CRN reflect an identical cognitive process, variations in CRN might be associated with dispositional characteristics as well. Higher CRN amplitudes have been found to reflect task engagement. In the present study, a simple-choice-reaction task was used to investigate ERN and CRN amplitudes in relation to their score on a conscientiousness scale. The task consisted of a simple rule that required pressing the left or right key when a circle or square appeared, respectively. During alternative conditions that occur infrequently, participants were instructed to violate or reverse the previously established response rules. Smaller ΔERN amplitudes (manifested in almost equal CRN and ERN amplitudes) and a tendency of better task performance from participants scoring high on the conscientiousness scale might indicate a greater focus on the task and higher motivation of responding correctly. In addition, higher Pc amplitudes directly following the CRN indicated that the response monitoring system of less conscientious participants showed a higher disengagement. The role of individual differences in CRN amplitude should be studied in future experiments on performance monitoring.